Skeletal muscle proteome of commercial broiler chickens as affected by pre slaughter electrical stunning - Md Saad, Salwani; Palliah, Jaya Vejayan; Idrus, Zulkifli; Sazili, Awis Qurni (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
The pre slaughter electrical stunning is no longer uncommon in halal poultry production nowadays. A sufficient amount of electrical current is applied through the brain to suppress its activity, which results in insensibility towards pain during the neck cutting until death. Proteomics is a field of study useful in unveiling information about proteins such as their identification, post-translational modification and responses towards external factors. It is likely that any intervention prior to slaughter may alter the post-mortem biochemical changes which can be determined through proteomics approach. To date, there is limited data to provide a better insight on the influence of electrical stunning on skelet al muscle proteome in broiler chickens. Hence, this study was conducted with an attempt to determine changes in skelet al muscle proteome of commercial broiler chickens subjected to pre slaughter electrical stunning. Fifty commercial broiler chickens (mixed–sex Cobb, at 42 days old, 2.60±0.2 kg) were randomly allotted to two treatment groups. Twenty five birds were manually shackled and subjected to water bath electrical stunning (at 30V, 0.2A and 50Hz, for 5 sec) prior to neck exsanguination, while the remaining 25 birds were shackled and slaughtered without any prior stunning. Pectoralis major muscle proteome was determined using 2-dimensional gel electrophoresis followed by MALDI-TOF/TOF mass spectrometry analysis. Muscles obtained from the electrically stunned birds presented two fold decreases in the expressions of beta enolase (p<0.05) and pyruvate kinase (p<0.05). All of these proteins belong to a group of enzyme in the glycolytic pathways responsible for generation of ATP. Thus, the decreased expressions of beta enolase, pyruvate kinase and glycogen phosphorylase suggest a possible reduction in the rate of glycogen metabolism following the electrical stunning.